Effects of Slide Storage on Detection of Molecular Markers by IHC and FISH in Endometrial Cancer Tissues From a Clinical Trial: An NRG Oncology/GOG Pilot Study. Issue 1 (January 2022) - Grushko, Tatyana A.; Filiaci, Virginia L.; Montag, Anthony G.; Apushkin, Marsha; Gomez, Maria J.; Monovich, Laura; Ramirez, Nilsa C.; Schwab, Carlton; Kesterson, Joshua P.; Seward, Shelly M.; Method, Michael W.; Olopade, Olufunmilayo I.; et al.
Abstract : We performed a pilot study in anticipation of using long-aged precut formalin-fixed paraffin-embedded tissue sections stored in real-world conditions for translational biomarker studies of topoisomerase 2A (TOP2A), Ki67, and human epidermal growth factor receptor 2 (HER2) in endometrial cancer. Formalin-fixed paraffin-embedded tissue blocks or unstained slides or both from GOG-0177 were collected centrally (1999-2000) and stored at room temperature. During 2004 to 2011 specimens were stored at 4°C. Matched pairs of stored slides and freshly cut slides from stored blocks were analyzed for TOP2A (KiS1), Ki67 (MIB1), and HER2 (HercepTest) proteins. To assess DNA stability ( HER2 PathVision), fluorescence in situ hybridization (FISH) was repeated on stored slides from 21 cases previously shown to be HER2 amplified. Immunohistochemistry (IHC) staining intensity and extent, mean FISH copies/cell, and copy number ratios were compared using the κ statistic for concordance or signed rank test for differences in old cut versus new cut slides. IHC results reflected some protein degradation in stored slides. The proportion of cells with TOP2A staining was lower on average by 12% in older sections ( P =0.03). The proportion of Ki67-positive cells was lower in stored slides by an average of 10% ( P <0.01). Too few cases in the IHC cohort were FISH positive for any conclusions. HER2 amplification by FISH was unaffected by slide storage. We conclude that use of aged stored slides for proliferation markers TOP2A and Ki67 is feasible but may modestly underestimate true values in endometrial cancer. Pilot studies for particular storage conditions/durations/antigens to be used in translational studies are warranted. Abstract : Supplemental Digital Content is available in the text.